Social Satire and Identity: An Analysis of Irony in Dritëro Agolli’s Poetry - Godime, Enida; Beshiri, Dalina (European Journal of Social Science Education and Research, 2026)
Irony plays an important role in the poetry of Dritëro Agolli and represents one of the most consistent ways through which his poetic voice engages with social reality, moral concerns, and questions of identity. This article examines the use of irony in a selection of Agolli’s poems written in different periods of his literary activity, with particular attention to verbal, situational, and Socratic irony. Using qualitative textual analysis and close reading, the study explores how irony creates distance between what is stated and what is implied, allowing the poet to reveal contradictions within political discourse, social behaviour, and individual self-perception. The analysis shows that irony in Agolli’s poetry does not function merely as a stylistic ornament, but as a reflective and critical tool that challenges false seriousness, exposes hypocrisy, and gives meaning to seemingly simple situations. Through irony, Agolli’s poetry invites the reader to question appearances and engage with values.